MentAllay : Islamic Mediation Application - Mounir, Ben Daia; Youssef, Chbani; Zulkifli, Zahidah (Multidisciplinary Applied Research and Innovation, 2022)
During the COVID-19 pandemic in Malaysia, adults in poor general health, which may reflect both physical and mental health, continue to report higher rates of depression than adults in good general health. The suicidal ideation that reached 468 in just the first 5 months of 2021, which is nearly equal to the annual number of suicides in 2020 and 2019. Thus, this project, MentAllay a mobile application aims to provide a secured virtual community where users can share their feelings and thoughts on handling their mental health. Besides that, it provides a various way to alleviate their stress and relax via Islamic guidance from various trusted sources. The application would help users to find the best verse that suits users’ current mood. This project has been carried out by using System Development Life Cycle (SDLC). For the data collection, interviews and surveys have been conducted from the people who has experience with mental health issues. The system has been developed by using Firebase. For the future enhancement, this application is expected can be implemented to not only IIUM community, but also can be generalised to any type of users.